Acceptance of Post Placental IUCD Among Antenatal Patients - Asma Yasin, Ayesha Azhar Khan, Asma Amin Baig, Madiha Afzal, Uzma Aziz, Heema (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To see the acceptance rate of PPIUCD among antenatal patients and compare it with international standards so that strategies to increase uptake of this contraceptive device can be devised especially for low compliance patients. Background : Post placental intrauterine contraceptive device ( PPIUCD) is the method of contraception that is effective immediately after delivery and patients don’t have to come back again from home. It is long acting, reversible, cost effective, free of systemic side effects and best for women with low compliance. Material and methods: This cross sectional observational study was carried out in outpatient department of obstetrics &gynaecology of Arif Memorial teaching hospital Lahore from January ary 2022 to March 2022. 285 pregnant patients irrespective of gestational age presenting to OPD were counselled for PPIUCD insertion after taking written informed consent. Results: Out of 285 patients counselled for PPIUCD insertion only 86 women (30%) accepted its insertion while 199 women (70%) refused for it. Majority of patients 205 (72%) were in age group 21-30 years, only 61(30%) of them accepted PPIUCD insertion and acceptance was highest (61%) in age group less than 20 years . 228 (80%) patients were literate and acceptance rate was 63% among them. Acceptance of PPIUCD was lower among multi para (22%) as compared to primipara (41%). Conclusion: Acceptance of PPIUCD in our antenatal mothers is poor. So ccounseling of antenatal women and their families will be helpful for high acceptance of PPIUCD.